2015
DOI: 10.3329/bpj.v18i1.23517
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of antibacterial activity of actinomycetes by co-culture with pathogenic bacteria

Abstract: In this study, we investigated the effect of pathogenic bacteria on the production of antibiotics by actinomycetes.We used four strains of actinomycetes-ANAM-5, ANAM-39, AIAH-10 and ANTS-1, which were isolated from the soils of Sundrabans, Bangladesh. All the strains were cultured in absence or presence of either alive or heatkilled human pathogens (Staphylococcus aureus and E. coli). The antibacterial activity of cultured cell-free supernatant fluid was analyzed by disc diffusion assay against the inducer str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This could be due to the ecological role such as defensive mechanism to maintain their niche, or invasion of an established microbial community [ 30 ]. It has been reported that live and heat-killed cells of S. aureus induced the production of secondary metabolites from marine microbial isolates [ 31 ]. About 119 microorganisms were screened and only 27 isolates were found active against one test organism [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to the ecological role such as defensive mechanism to maintain their niche, or invasion of an established microbial community [ 30 ]. It has been reported that live and heat-killed cells of S. aureus induced the production of secondary metabolites from marine microbial isolates [ 31 ]. About 119 microorganisms were screened and only 27 isolates were found active against one test organism [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…"Further improvement of the system of continuing education, increasing the capacity of quality educational services, continuing the policy of training highly qualified personnel in accordance with the modern needs of the labor market" were identified as priorities in the field of medical education. In today's pandemic, the requirements for training doctors with modern knowledge, developing their professional competence, increasing their social activity are characterized by the above [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%